2010
DOI: 10.1007/bf03245871
|View full text |Cite
|
Sign up to set email alerts
|

Application of aqueous mixtures of polypropylene glycol or polyethylene glycol with salts in proteomic analysis

Abstract: Partitioning of Bovine serum albumin (BSA), ȕ-lactoglobulin (ȕ-LG) and zein as model proteins in aqueous two-phase systems (S) containing polypropylene glycol (PPG425) or polyethylene glycol (PEG 6000) and salts (MgSO 4 , (NH 4 ) 2 SO 4 , Na 2 SO 4 ) is presented in this paper. The effects of different factors such as tie-line length, salt type and polymer type on the partition coefficient and recovery percent of proteins were analysed. The model proteins were separated by these systems (S) and directly used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Although the most abundant proteins in E. coli are still considered hydrophilic (negative values in hydrophobicity scale), GFP is even more hydrophilic, and thus, this can explain the difference in the migration pattern in the polymer/ [Ch]Cl ABS. This effect was also observed by Salabat et al 62 in a study with different polymer/salt-based ABS (polymers PPG-425 and PEG-600), where the PPG-425 systems had the best results for the selective separation of hydrophobic and hydrophilic proteins. Additionally, we have demonstrated that the integration of PEG/NaPA + [Ch]Cl and PEG/[Ch]Clbased ABS, two purification platforms with different protein partitioning mechanisms, can be a feasible approach to increase the protein purification abilities.…”
Section: ■ Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Although the most abundant proteins in E. coli are still considered hydrophilic (negative values in hydrophobicity scale), GFP is even more hydrophilic, and thus, this can explain the difference in the migration pattern in the polymer/ [Ch]Cl ABS. This effect was also observed by Salabat et al 62 in a study with different polymer/salt-based ABS (polymers PPG-425 and PEG-600), where the PPG-425 systems had the best results for the selective separation of hydrophobic and hydrophilic proteins. Additionally, we have demonstrated that the integration of PEG/NaPA + [Ch]Cl and PEG/[Ch]Clbased ABS, two purification platforms with different protein partitioning mechanisms, can be a feasible approach to increase the protein purification abilities.…”
Section: ■ Introductionsupporting
confidence: 76%
“…Thus, because of the hydrophilic character of GFP, the hydrophobic–hydrophilic interactions had a major role in the partition mechanism for both ABS, where the GFP partitioned always for the phase with the highest water content. Previously, Salabat et al performed some studies on protein extraction using polymer/salt ABS (by combining PEG-600 and PPG-425 polymers and MgSO 4 , Na 2 SO 4 , (NH 4 ) 2 SO 4 inorganic salts), demonstrating a selective extraction of hydrophobic protein for the polymeric phase and the partition of the hydrophilic proteins toward the salt-rich phase. The partition of GFP using other type of polymer/salt ABS was previously reported (PEG with salts MgSO 4 , Na 3 C 6 H 5 O 7 , (NH 4 ) 2 SO 4 , Na 2 SO 4 or buffer NaH 2 PO 4 + Na 2 HPO 4 ), , but usually exhibiting quite low purification capacity (as will be further discussed in the next sections), thus requiring the association of other techniques like chromatography to significantly increase the purification levels.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As partições de oito biomoléculas modelo, dentre elas a lisozima, foi estudada por Perez et al (2013) em SABs formados por PEG (4000, 6000 ou 8000) e sais biodegradáveis (succinato de sódio, tartarato de sódio ou citrato de sódio) na temperatura de 22°C e pH 5,0. O efeito de diferentes polímeros (polipropileno glicol (PPG 425) ou PEG 6000) e sais (sulfato de magnésio, MgSO4; sulfato de amônio, (NH4)2SO4; ou sulfato de sódio, Na2SO4) no comportamento de partição de diferentes proteínas modelo (BSA, β-LG e zeína) foram estudadas em detalhes por Salabat et al(2010). A BSA e β-LG são hidrofílicas e particionaram para a fase inferior dos SABs e a zeína (proteína do grão de milho) que é hidrofóbica teve preferência pela fase superior.…”
Section: -Publicações Sobre Partições Em Sabs E Ellunclassified